Interventions aiming to improve menstrual, sexual, reproductive, and mental health among out-of-school girls: a systematic review - Farquharson, Karinn; Quinn-Savory, Alexandra; Zulaika, Garazi; Mason, Linda; Nungo, Susan; Nyothach, Elizabeth; Unger, Holger; Sivakami, Muthusamy; Spinhoven, Philip; Phillips-Howard, Penelope A.; van Eijk, Anna Maria (Frontiers in Public Health, 2024)
PurposeOut-of-school adolescent girls (OoSGs) can lack education on menstrual, sexual, reproductive, and mental health (SRMH) and be more vulnerable to SRMH harms. Targeted interventions could reduce these risks. We assessed interventions and their effectiveness among OoSGs globally.MethodsSix online databases were searched for interventional studies targeting SRMH problems in OoSGs. Two coders independently abstracted data from each eligible study, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. We summarized results using forest plots.ResultsA total of 1,244 studies were screened; eight studies with sufficient information on SRMH outcomes were included (9,084 OoSGs, range 100–3,026 per study, overall study quality low-to-moderate). Six were educational programmes, and two were cash interventions; no study was directed at mental health. Participants were recruited through village census, outreach workers, and work locations. Some improvements were seen in indicators of SRMH knowledge (four studies), attitudes (one study), and risky sexual behaviors (four studies); however, no reduction was seen in human immunodeficiency virus or herpes simplex virus-2 incidence (two studies).DiscussionThis review suggests that programmes can improve OosG’s SRMH knowledge, attitudes, and practices and can be delivered in low resource contexts. Effective interventions are needed to support OoSGs, including interventions focusing on SRMH support incorporating elements of cash-transfer, and comprehensive sexual education, and to aid local policy and programming.